The investigation on effect of wind trade to precipitation in Kuantan, Pahang - Nurul Asyikin, Wahid (2014)
The rainfall distribution is spatial and temporal variability. The development and intensity of rainfall is governed and influenced by monsoon systems, orographic convective systems and land-sea interactions. Monsoons are seasonal winds, and develop around thermally produced continental highs in winter and lows in summer. North-east monsoon wind, also known as trade-wind brings heavy rainfall to Kuantan District, part of east-cOast Peninsular Malaysia that causes flooding. This study was to investigate the impact of trade-wind to precipitation during 2013 flood events at Kuantan District, Pahang. The specific objectives are as follows; to established satellitebased rainfall intensity database and wind direction using Geographical Information System and to analyse rainfall distributions intensity effect of wind direction. Tropical Rainfall Measuring Mission (TRMM) satellite-based rainfall intensity data and wind data from Meteorological Malaysia Department (MMD) were used to establish a database. Further, satellite-based rainfall intensity distribution and wind direction had been map. Therefore, relationship between rainfall intensity distribution and wind direction were analysed. The result shows, during research most direction of wind come from North North West (NNW), not as stated by previous research. This causing more rainfall distribution intensity in the South South East region of district. Consequently, flooding occurred at that area. In general, rainfall distribution intensity influenced by wind direction, meanwhile in local area topography affects wind direction.